Testing the Activity of Chitosan Nanohydrogel from Belut Sawah (Monopterus albus) Extract as a Future Anti-Aging Candidate - Ratih anggraeni; Romauli Anna Teresia Marbun (Jurnal FARMASIMED (JFM), 2025)
Background: Premature aging has become a serious concern, especially among women. The aging process can occur at any time and progress rapidly. This condition may be caused by exposure to sunlight, which induces the formation of Reactive Oxygen Species (ROS) in the skin. When the amount of ROS exceeds the antioxidant defense capacity of skin cells, it can lead to dryness, thinning, loss of elasticity, wrinkles, and even skin cancer. The swamp eel (Monopterus albus) is commonly used as food by the community. Previous studies have shown that eel extract has been used to treat incision wounds, gastric ulcers, and anemia. It contains vitamin A, vitamin B, and selenium. This species is abundantly found in rice fields and muddy ponds in the Lubuk Pakam area. The formulation of the extract into nan chitosan derived from shrimp shells has been reported to improve the delivery of antioxidant effects into the skin layers. Objective: This study aimed to analyze the activity of a hydrogel combining swamp eel extract with nanochitosan, evaluate its antioxidant activity, and assess the physical stability of the hydrogel formulation as an anti-aging preparation. Methods: Extraction was carried out using the maceration method. The nanochitosan-based hydrogel formulation was designed to enhance the delivery of the eel’s active compounds. Antioxidant activity was tested using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method, and the physical stability of the hydrogel was evaluated. Results: The physical evaluation showed that the nanochitosan hydrogel containing swamp eel extract maintained good stability during storage. Organoleptic tests indicated a consistent yellowish-white color, characteristic aroma, and uniform texture (homogeneity) from day 0 to day 4. The pH value remained stable at 5.2 throughout weeks 0 to 4, within the physiological range of skin pH. Viscosity measurements were 10,350 cps for F1, 11,750 cps for F2, and 23,650 cps for F3. These findings suggest that the formulation possessed good physical stability and an appropriate consistency for topical application. Conclusion: Skin elasticity and biological activity tests showed an increase in skin firmness, likely due to the collagen, flavonoid, and antioxidant content in the swamp eel extract. Irritation and panelist preference tests confirmed its safety and user acceptability. Therefore, this hydrogel shows potential to be developed as a natural, safe, and consumer-friendly anti-aging formulation.